The Effect of Knowledge, Attitude, and Parents Behavior Towards Sex Education Parents With Sexual Violence Incident - Andari, Istiqomah Dwi; Woro, Oktia; Yuniastuti, Ari (Universitas Negeri Semarang, 2019)
Sexual abuse of children is a serious problem because it leads to losses and traumatic. The high sexual abuse of children showed the importance of knowledge, attitude and behavior of parents. Obtain information about the role of parents towards pendididkan oarang sex in cases of sexual abuse of junior high school student.This study used a qualitative approach supported by quantitative data, using interviews to parents who met the inclusion criteria by purposive sampling. Using a cross sectional study design with primary and sekundery data.Variabel of this study isÃ‚Â include Knowledge, Attitude and Parents Behavior. Effect of knowledge, attitude and behavior of parents about sex education on the incidence of sexual harassment. Parents understanding to provide early sex education to children before sexually abused. The influence of parents' attitudes tend to be a lot better. Parents who behave well to give sex education to their children. The benefits of research can help health institutions in relation to health promotion policy decisions related to handling the incident of sexual violence experienced by children in junior high.